2016
DOI: 10.1080/19420862.2016.1229722
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and pharmacodynamics of DSTA4637A: A novel THIOMAB™ antibody antibiotic conjugate against Staphylococcus aureus in mice

Abstract: DSTA4637A, a novel THIOMAB™ antibody antibiotic conjugate (TAC) against Staphylococcus aureus (S. aureus), is currently being investigated as a potential therapy against S. aureus infections. Structurally, TAC is composed of an anti-S. aureus antibody linked to a potent antibiotic, dmDNA31. The goal of the current study was to characterize the pharmacokinetics (PK) of TAC in mice, assess the effect of S. aureus infection on its PK, and evaluate its pharmacodynamics (PD) by measuring the bacterial load in vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
77
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(91 citation statements)
references
References 14 publications
3
77
0
Order By: Relevance
“…The conjugate ( 100 ), also known as DSTA4637S, was composed of an anti‐ S. aureus THIOMAB TM antibody ( 101 ) (a human IgG1 mAb generated by Genentech Inc, South San Francisco, CA), a protease cleavable valine‐citrulline linker (maleimido‐caproyl‐valine‐citrulline‐para‐aminobenzyl) and a potent antibiotic, dmDNA31 ( 102 ) (rifalog, 4‐dimethylamino piperidino‐hydroxybenzoxazino rifamycin) (Figure A). ( 102 ) was covalently linked to anti‐ S. aureus antibody through cysteine residues to yield an average antibiotic to unconjugated antibody ratio of ~2 . The in vitro evaluation showed that ( 100 ) was capable of eradicating intracellular S. aureus infections observed in every infected cell type tested, including human macrophages, endothelial and epithelial cell lines.…”
Section: Other Antimicrobial‐carrier Conjugatesmentioning
confidence: 99%
See 3 more Smart Citations
“…The conjugate ( 100 ), also known as DSTA4637S, was composed of an anti‐ S. aureus THIOMAB TM antibody ( 101 ) (a human IgG1 mAb generated by Genentech Inc, South San Francisco, CA), a protease cleavable valine‐citrulline linker (maleimido‐caproyl‐valine‐citrulline‐para‐aminobenzyl) and a potent antibiotic, dmDNA31 ( 102 ) (rifalog, 4‐dimethylamino piperidino‐hydroxybenzoxazino rifamycin) (Figure A). ( 102 ) was covalently linked to anti‐ S. aureus antibody through cysteine residues to yield an average antibiotic to unconjugated antibody ratio of ~2 . The in vitro evaluation showed that ( 100 ) was capable of eradicating intracellular S. aureus infections observed in every infected cell type tested, including human macrophages, endothelial and epithelial cell lines.…”
Section: Other Antimicrobial‐carrier Conjugatesmentioning
confidence: 99%
“…This ACC conjugate ( 100 ) was recently assessed for its pharmacokinetic (PK) and pharmacodynamics (PD) profiles in S. aureus ‐infected and noninfected mice models over a dosage range of 25 to 50 and 5 to 50 mg/kg, respectively . The results showed that a single intravenous dose of DSTA4637A (a preclinical formulation of ( 100 )) exhibited a PK behavior similar to that in the noninfected mice, and could significantly reduce bacterial load in the heart, kidney, and bones after both 7 and 14 days of treatment . Conjugation of dmDNA31 with a THIOMAB antibody improved the half‐life ( t 1/2 ) of the antibiotic in vivo, extending the t 1/2 from 3 to 4 hours to 4 days.…”
Section: Other Antimicrobial‐carrier Conjugatesmentioning
confidence: 99%
See 2 more Smart Citations
“…The binding of a host macromolecule to a receptor, followed by the internalisation of the complex, provides a potential route to specifically deliver therapeutics into trypanosome cells. Entry of TLF1 via the HpHbR and the release of a cytotoxin after internalisation is analogous to the mode of action of ADCs (20), a growing class of therapeutics, particularly used in applications in oncology(2123) and also with demonstrated potential as anti-bacterials(24, 25). An early attempt to develop ADCs against the intracellular American trypanosome, Trypanosoma cruzi , used chlorambucil conjugated to polyclonal IgGs purified from chronically infected rabbits (26) and, while results were promising, this was only partially successful.…”
Section: Introductionmentioning
confidence: 99%